Kualiti Perkhidmatan Perbankan Islam dan Kepuasan Pelanggan - Khairul Nizam, Mamat @ Muhammad (2003)
The objective of this study is to determine the relationship between the dimension of service quality in Islamic Banking and customer satisfaction. The study based on the CARTER instrumentation was introduced by Qawi and Lynn (2001) was adaptation form SERVQUAL instrument developed by Parasuraman et. al (1985). The CARTER instrumentation was used to measure six dimension of service quality in Islamic banking; i) compliance, ii) assurance iii) reliability, iv) tangible, v) empathy and vi) responsiveness. The relationship between dimension of service quality in Islamic banking and customer satisfaction was observed. To measure the service quality of Bank Islam Malaysia Berhad and Bank Muamalat Malaysia Berhad the statistical analysis Correlation, t-test and ANOVA was used in this study. The sample consisted of 271 respondents from 2 Islamic Bank, Bank Islam Malaysia Berhad and Bank Muamalat Malaysia Berhad. The finding of this study indicated that there was a significant relationship between dimension of service quality in Islamic banking and customer satisfaction. Reliability, empathy, and responsiveness analysis showed that there was a strong significant influence on customer satisfaction in Islamic banking.